A high linearity CMOS RF amplifier for power control module in RFID reader - Uddin, Md. Jassim.; Ibrahimy, Muhammad Ibn; Nordin, Anis Nurashikin; Mohammad Ali, Masni (2008)
Radio frequency identification (RFID) is the latest technology for automatic identification, which allows the transmission of a unique serial number wirelessly. Power control module of RFID reader is used to perform digital signal processing techniques and procedures over the received data from the RFID readers. A high linearity CMOS RF (radio frequency) power amplifier has the advantage of being low-cost and easily integrated on chip. It has become the smart technology of choice for wireless devices (RFID readers). This work demonstrates a 3.3V single voltage self-biased 2.4GHz– 2.5GHz high linearity RF power amplifier for RFID applications. The proposed amplifier achieved 81.1 dB gain, output power at P1dB -4.0 dBm, 1-dB gain compression power with 10.0% power efficiency (PE) and 17.4% power-added efficiency (PAE). Furthermore, high linearity with 1.6dBc for IM3, -6.633dBm and -2.887dBm third-order intercept point IIP3 and OIP3 at frequency of 2.45GHz is also measured. The Adjacent Channel Power Ratio (ACPR) has been achieved -7.26dBc for input port and -1.0dBc for output port. The amplifier also exhibited very good isolation of 2.85dB, the insertion loss of 0.8dB and return loss of 9.94dB. Simulations were conducted using Mentor Graphic software tools.